Analisis Konflik Kelas Luring Pada Pendidikan Anak Usia Dini di Masa Pandemi COVID-19 - Wening Purbatin Palupi Soenjoto (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
Early childhood education in Indonesia is still an education that is starting to be of interest to parents to direct their children's readiness to continue their education to the next stage. With the learning process of self-development, cognitive processing, emotional processing, psychomotor processing and social interaction exercises in the form of children's independence during their playing period. Early childhood education is also different from other levels of education, it is only trained to play a lot but there is still learning. However, since the COVID-19 pandemic in early 2019 until now, early childhood education has been affected and online classes are held, in addition to students, including the age vulnerable to disease, are also still the lack of understanding of early childhood interpreting the covid 19 virus like adults. The psychological shock experienced by children when they have to go to school at home, not meeting teachers and friends will lead to boredom, lazy to do assignments so that they are affected by the psychological slumber felt by parents, especially mothers who have to teach children at home, who were previously children's learning tasks. more handled by teachers in schools. With online classes it is considered the best solution to hack the spread of covid 19 in the environment of early childhood. The emergence of conflicts between online and offline classes in the world of early childhood education is the basis for the research of this article, which uses qualitative research methods and is described in a descriptive analysis based on literature review and studies of social phenomena.